Innovation Input Dynamics of Polish Regions - Perska, Anita (Studia Oeconomica Posnaniensia, 2013)
This paper discusses the dynamics regarding the innovation input of regions. The analysis of innovation input includes such features as the proportion of the population aged 25-64 years participating in lifelong learning in the region; human resources in science and technology (HRST) as a percentage of the economically active population; and the proportion of workers with higher education in the total number of employees in the region. The aim of this paper is to describe selected characteristics of the innovation input of Polish regions in the years 2001 and 2010, identify differences between 2001 and 2010, and determine the average annual rate of change. In addition, the regions are classified according to the dynamics of the innovation input in 2010 as compared to 2001. On the basis of the literature and preliminary observations an assumption is made that the regions are diversified in terms of innovation input and a hypothesis is put forward that for most regions the values relating to the dynamics of innovation input are lower or higher than the median, thus assigning them to extreme categories.